Gender sebagai variabel moderasi pada pengaruh gaya hidup terhadap pengelolaan keuangan - Melisa, Dyna; Mardiana, Mardiana (Jurnal Riset Pendidikan Ekonomi, 2025)
This research examined the extent to which lifestyle affects Generation Z's financial management, with gender as a moderating factor. The method in this study uses quantitative methods. The population in this study is generation Z of Malang city. The sample used in this study amounted to 100 respondents using the Lameshow formula sampling technique. The data used in this study is primary data, namely by distributing questionnaires. The data obtained was then analyzed using validity, reliability, and MRA tests through the SmartPLS 3.0 application. The results of the analysis show that lifestyle has a significant influence on an individual's ability to manage finances. The more consumptive a person's lifestyle, the worse their control over financial management. Conversely, if their lifestyle is more controlled, their financial management is better. In addition, the results revealed that gender does not moderate the relationship between lifestyle and financial management. Both men and women show results where their financial patterns are the same, so gender factors do not strengthen or weaken the relationship. Given that a consumptive lifestyle can hinder financial management, it is necessary to reduce consumptive behavior through simple lifestyle behavior education without differentiating strategies based on gender. This is because their behavior patterns towards financial management influenced by lifestyle are relatively similar.